2008
DOI: 10.1111/j.1439-0523.2007.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of nutrient components in maize kernels under low nitrogen conditions

Abstract: A set of 213 F 2:3 families were used to investigate the effects of nitrogen (N) on grain yield and the concentrations of three nutrient components in maize (Zea mays L.) kernels. A genetic linkage map was constructed using 189 SSR (simple sequence repeat) markers, spanning a total of 2003 cM, including 11 linkages, and the families were evaluated under high N and low N conditions at two farm locations. The results indicate that low N conditions may induce an increase in starch concentration, but a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
5
11
1
1
Order By: Relevance
“…While N is a component of protein, so it inferred that lack of nitrogen might reduce grain N content greatly. The similar results also reported by Liu et al (2008) in maize, they showed that the grain yield, grain protein and oil contents in F 2:3 /F 2:4 populations were significantly reduced, but the starch a little increased under Nconditions compared with N+ conditions at two locations.…”
Section: Introductionsupporting
confidence: 88%
“…While N is a component of protein, so it inferred that lack of nitrogen might reduce grain N content greatly. The similar results also reported by Liu et al (2008) in maize, they showed that the grain yield, grain protein and oil contents in F 2:3 /F 2:4 populations were significantly reduced, but the starch a little increased under Nconditions compared with N+ conditions at two locations.…”
Section: Introductionsupporting
confidence: 88%
“…또 다른 최근 개발된 옥수수 주요 유전자원으로는 NAM(Nested Association Mapping) 집단이 있는데, NAM 집단(population)은 245 개의 집단에 서 200 개씩 총 5000개의 RIL 계통을 구축해 놓은 옥수수 유전자원 집단이다 (Fig. 1(A) (Liu et al, 2003;Flint-Garcia et al, 2005;Liu et al, 2008). NAM 집단에 사용된 대표적 인 교배친들로는 Suwan(태국계통), Ki3(한발 감수성), Ki11 (한발 저항성) 등이 교배친으로 이용되었으며, 또한 CIMMYT 에서 개발한 열대성 품종 8개(CML52, CML69, CML103, CML228, CML247, CML277, CML322, CML333) 등이 이 용되었다 을 얻을 수 있는 반면 (Messmer et al, 2009;Szalma et al, 2007) (Tuberosa et al, 2002b;Campos et al, 2004;Xu et al, 2009).…”
Section: Ngs(next-generation Sequencing)unclassified
“…Currently, most maize in the world is grown under N-deficient conditions because of low N use efficiency, limited availability of fertilizer or low purchasing power of farmers (Ribaut et al, 2007). From the literature, different N regimes have been frequently used to detect QTLs in plant such as rice (Oryza sativa L.) (Lian et al, 2005), maize (Liu et al, 2008) and wheat (Triticum aestivum L.) , but studies on QTL mapping for maize KNE under different N regimes have been rarely reported (Agrama et al, 1999). Accordingly, it is meaningful that different N regimes that affect KNE in maize are used for QTL mapping.…”
Section: Introductionmentioning
confidence: 99%